2016
DOI: 10.14742/ajet.2306
|View full text |Cite
|
Sign up to set email alerts
|

EFL learners’ strategy use during task-based interaction in Second Life

Abstract: Motivated by theoretical and pedagogical concerns that the link between second language (L2) learners' second language acquisition (SLA) and language use in 3D multi-user virtual environments (MUVEs) is still not fully connected in current SLA literature, this study examined the patterns of English as a foreign language (EFL) learners' employment of communication strategies during task-based interaction in Second Life (SL). Nine adult EFL learners worldwide were recruited, and they used their avatars to negoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 31 publications
(39 reference statements)
3
30
0
1
Order By: Relevance
“…The nature of openness and flexibility makes SL an optimal platform to create more opportunities for real-world task simulation, which could be cumbersome to carry out in a physical class (Dawley & Dede, 2014;Gonz alez-Lloret & Ortega, 2014). Despite those positive claims, technical glitches encountered in SL have also been reported, such as platform instability, poor quality of audio output and echoing, demand for more advanced hardware, and internet connection interruption (Chen, 2016a(Chen, , 2016bDawley & Dede, 2014;Kozlova & Priven, 2015;Petrakou, 2010;Peterson, 2010). These caveats need to be taken into account in order to preempt SL malfunctions that may backfire on well-planned lessons and students' learning experiences.…”
Section: Literature Review Language Teachers In Slmentioning
confidence: 99%
See 2 more Smart Citations
“…The nature of openness and flexibility makes SL an optimal platform to create more opportunities for real-world task simulation, which could be cumbersome to carry out in a physical class (Dawley & Dede, 2014;Gonz alez-Lloret & Ortega, 2014). Despite those positive claims, technical glitches encountered in SL have also been reported, such as platform instability, poor quality of audio output and echoing, demand for more advanced hardware, and internet connection interruption (Chen, 2016a(Chen, , 2016bDawley & Dede, 2014;Kozlova & Priven, 2015;Petrakou, 2010;Peterson, 2010). These caveats need to be taken into account in order to preempt SL malfunctions that may backfire on well-planned lessons and students' learning experiences.…”
Section: Literature Review Language Teachers In Slmentioning
confidence: 99%
“…Notably, prior studies have been geared more towards learner-based research, targeting SL as a potential language learning environment (Chen, 2016a(Chen, , 2016b(Chen, , 2018Canto, de Graaff, & Jauregi, 2014;Deutschmann & Panichi, 2013;Lan et al, 2015;Peterson, 2010Peterson, , 2012. Research focusing on the impact of 3D virtual teaching on language teachers' professional development and beliefs is relatively scarce.…”
Section: Literature Review Language Teachers In Slmentioning
confidence: 99%
See 1 more Smart Citation
“…Couple of Project meetings was done on the plot to gather experience and observe the possible problems and solutions (Ibanez, Garcia, Galan, Maroto, Morillo & Kloos, 2011). Chen (2016). has observed that recently distance education has given a new platform for learning i.e.…”
Section: Purpose Of Studymentioning
confidence: 99%
“…This type of learning environment increases the learning motivation (Gajňáková, Vaculík & Vaško, 2010). Resultantly, the participants involves in taking risks while actively participate in the learning of a foreign language (Chen, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%